Communications Guide for Startups How to Win Customers, Investors, and new Talent through Inspiring Messaging - Prexl, Lydia 1985- (UVK Verlag, 2022)
Turning communication into your start-up's biggest asset Nine out of ten startups fail. One cause of failre is bad communication - both externally and internally. Yet there is little systematic advice on how startups and scale-ups can overcome this challenge and inspire all stakeholders around the company's vision, values, and offering. This book closes this gap - with seventy experts sharing their learnings and experiences. It is a guide for all curious to learn more about how to win customers, investors and new talent through a convincing narrative, covering external, internal, social media and leadership communication